Sofrimento psicológico, expressão e ficção: uma análise do romance Kindred: Laços de Sangue de Octavia E. Butler - Sabino Vieira, Gabrielle (Universidade Federal de São Carlos, 2024)
The aim of this study is to analyse Octavia E. Butler's Kindred: Blood Ties, a historical novel set in the field of science fiction literature. The proposed analysis is based on psychoanalysis, taking into account its understanding of a method of investigation and construction of knowledge that is based on interpretation using psychoanalytic processes and concepts. The studies and reflections proposed here include the study of literature and psychoanalysis and their dialogue, especially the following points: guilt in the malaise of culture, the civilisational pact, based on Freudian texts: The Malaise of Civilisation and Psychology of the Masses and Analysis of the Self. We will also use Frantz Omar Fanon, who dialogues with psychoanalysis and the relationship between violence as a means of subjectification in the face of colonial dehumanisation.
Psychological suffering, expression and fiction: an analysis of the novel Kindred: Blood Ties by Octavia E. Butler
Keywords: Psicanálise; Literatura; Octavia E. Butler; Violência; Suicídio; O Mal-Estar na Civilização; Psychoanalysis; Literature; Violence; Suicide; Malaise in Civilisation; CIENCIAS HUMANAS::PSICOLOGIA